(untitled) (Research, Society and Development, 2024)
Obesity is a chronic condition associated with an elevated risk of diseases and premature death, with more than half of the Brazilian population facing overweight and obesity. The complexity of obesity involves genetic, environmental, and psychological factors of the individual and is often linked to Binge Eating Disorder (BED) which negatively impacts quality of life and requires specialized clinical and nutritional attention. The objective was to investigate the relationship between BED in adults with overweight and obesity. This is an observational and descriptive study, with data collected through an online survey of 65 adults with overweight or obesity, using a nutritional anamnesis questionnaire and the Binge Eating Scale (BES). Statistical data analyses were performed using SPSS software. Greater severity of BED was observed, especially in women, correlated with Body Mass Index (BMI). No individuals with elevated BMI were free of eating disorders, emphasizing the importance of diagnosing and treating this condition in adults with BMI ≥ 25 kg/m².